PENETAPAN KADAR KALSIUM SECARA KOLORIMETRI PADA CANGKANG KERANG HIJAU (Perna viridis) JANTAN DALAM FORMULA PASTA GIGI - SIHOMBING, IWEL SUDARNO; NURBAYA, SITI (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The shell of the male green mussel (Perna viridis) contains several minerals including calcium which is needed by the human body. Green scallop shells have a fairly high calcium content. This study aims to determine the calcium levels in green mussel shells and in the preparation of green mussel shell toothpaste. This type of research is experimental with colorimetric method using spectrophotometric equipment, namely UV visible spectrophotometer or visible light. Evaluation of the preparation includes organoleptic tests, homogeneity, pH, dispersion and foam formation. Quantitative analysis was carried out at a maximum wavelength of 505.00 nm and obtained the line equation linear regression, namely y = 0.0802X + 0.0109 with a correlation value (r) of 0.9976. The results showed that the calcium content in green mussel shells was 86.517 g/100g, the calcium content in the Formula I toothpaste was 19.874 g/100g and the calcium content in the Formula II toothpaste was 27,613 g/100g.